Fig. 24. A in Cambrian microfossils from glacial erratics of King George Island, Antarctica - Wrona, Ryszard (Zenodo, 2004)
Fig. 24. A. Diagrammatic cross−section of the wall of Mongolitubulus squamifer Missarzhevsky. B. Energy dispersive spectrum (EDS) for the M. squamifer sclerite. C. Broken end of the specimen figured in Fig. 23D, showing layered wall structure including outer hyaline layer and fibrous inner layer. Published as part of Wrona, Ryszard, 2004, Cambrian microfossils from glacial erratics of King George Island, Antarctica, pp. 13-56 in Acta Palaeontologica Polonica 49 (1) on page 48, DOI: 10.5281/zenodo.13285795